Determinação do potencial aromático de vinhos espumantes cujos vinhos base foram elaborados com leveduras Saccharomyces e Torulaspora delbrueckii - Ferreira, Daniel de Siqueira (My University, 2019)
This study had as an objective evaluate sparkling wines produced by the traditional method witch the base wine was made of Chardonnay grapes fermented with Saccharomyces and non-Saccharomyces yeasts, from the 2015 harvest of Serra Gaúcha, Rio Grande do Sul. Six fermentation processes (treatments), composed of two yeast arrays: Saccharomyces cerevisae and Torulaspora delbrueckii, both commercial, applied to the base wine. The different treatments consisted of two treatments with pure cultures, one sequential inoculation and three co-inoculations at different concentrations of yeasts. Afterwards, the obtained sparkling wines were evaluated as a function of time, performing analyzes with intervals of three months between them. The parameters analyzed were: classic analyzes of wines, methanol, ethanal, higher alcohols, esters and volatile acids, tyrosol, color index, total phenolic compounds, phenolic acids, catechins and epicatechins. The sparkling wines elaborated with 100% of Saccharomyces cerevisae showed higher concentrations in residual sugars and alcoholic strength. The higher alcohols presented higher concentrations at the sparkling wines made with the non-Saccharomyces yeasts, presenting higher levels in the treatment with 100% of Torulaspora delbrueckii (T6). Although there is a higher concentration of higher alcohols in the treatment with non-Saccharomyces yeasts, they are still within acceptable levels for a quality wine. Small differences in the results of methanol, ethanal and hexanol and trans-3-hexan-1-ol were observed. Sequential inoculation of yeasts Saccharomyces cerevisae and Torulaspora delbrueckii (1:1) resulted in higher concentration of 2-phenylethanol in relation to the other treatments. The esters of acetic acid did not present significant differences between the treatments, except for 2-phenyl ethyl acetate, which showed differences between the fermentation with sequential inoculation (1:1) and the fermentation with 100% Torulaspora delbrueckii and ethyl acetate, whose highest concentration occurred in the sparkling wines where wine fermentation occurred with 100% Torulaspora delbrueckii. The fatty acid esters presented, in general, higher concentrations in the treatments whose proportions of Torulaspora delbrueckii were larger. Diethyl succinate presented the highest concentration in the treatment with the sequential inoculation (T5) for all evaluated times. Volatile acids had lower concentrations in treatments where Torulaspora delbrueckii was present in greater proportion (200:1 co-inoculation, sequential 1:1 and 100% Torulaspora delbrueckii). The differences between the treatments were not very representative for the total phenolic compounds, color 11 index, catechins, epicatechins and phenolic acids of the cinnamic series. The time variable was the main responsible for the observed variations and the yeasts used in the work had little influence on the results. This work allowed to show the aromatic differences between the elaborated sparkling wines with Saccharomyces and non-Saccharomycese new studies should evaluate other characteristics of the sparkling wines as protein stability and formation in order to improve the profile of the national sparkling wines.
Este estudo teve como objetivo avaliar espumantes elaborados pelo método tradicional, com vinho base de uvas Chardonnay fermentados com leveduras Saccharomyces e não-Saccharomyces, provenientes da safra de 2015 da Serra Gaúcha, Rio Grande do Sul. Foram analisadas as diferenças entre seis processos de fermentação (tratamentos), compostos por arranjos de duas leveduras: Saccharomyces cerevisae e Torulaspora delbrueckii, ambas comerciais e aplicadas ao vinho base. Os diferentes tratamentos consistiram em dois tratamentos com culturas puras, uma inoculação sequencial e três co-inoculações em diferentes concentrações de leveduras, totalizando seis tratamentos. Na sequência, os espumantes obtidos, foram avaliados em função do tempo, realizando análises trimestrais durante um ano. Os parâmetros analisados foram: análises clássicas dos vinhos, metanol, etanal, álcoois superiores, ésteres e ácidos voláteis, tirosol, índice de cor, compostos fenólicos totais, ácidos fenólicos, catequinas e epicatequinas. Os espumantes elaborados com 100% de Saccharomyces cerevisae apresentaram maiores concentrações em açúcares residuais e título alcoométrico e o menor nível em tirosol. Os álcoois superiores, apresentaram maiores concentrações nos espumantes elaborados com as leveduras não-Saccharomyces, apresentando maiores níveis no tratamento com 100% de Torulaspora delbrueckii (T6). Apesar de haver uma maior concentração de álcoois superiores no tratamento com leveduras não-Saccharomyces, estes ainda se apresentam dentro dos níveis admissíveis para um vinho de qualidade. Em todos os tratamentos, observou-se pequenas diferenças nos resultados de metanol, etanal e nos álcoois hexanol e trans-3-hexan-1-ol. A inoculação sequencial das leveduras Saccharomyces cerevisae e Torulaspora delbrueckii (na razão de 1:1), resultou em maior concentração de 2-feniletanol em relação aos demais tratamentos. Os ésteres do ácido acético não apresentaram diferenças significativas entre os tratamentos, com exceção do acetato de 2-fenil etila, que apresentou diferenças entre a fermentação com inoculação sequencial e a fermentação com 100% Torulaspora delbrueckii e do acetato de etila, cuja maior concentração ocorreu nos espumantes onde a fermentação dos vinhos ocorreu com 100% Torulaspora delbrueckii. Os ésteres dos ácidos graxos apresentaram, em geral, maiores concentrações nos tratamentos cujas proporções de Torulaspora delbrueckii eram maiores. O dietil succinato apresentou a maior concentração no tratamento com a inoculação sequencial (T5) para todos os tempos avaliados. Os ácidos voláteis apresentaram menores concentrações nos tratamentos em que a Torulaspora delbrueckii está presente em 9 maior proporção (co-inoculação 200:1, sequêncial 1:1 e 100% Torulaspora delbrueckii). As diferenças entre os tratamentos se revelaram pouco representativas para os compostos fenólicos totais, índice de cor, catequinas, epicatequinas e ácidos fenólicos da série cinâmica. A variável tempo foi a principal responsável pelas variações observadas nestes compostos e as leveduras utilizadas no trabalho, pouco influenciaram nos resultados. Este trabalho permitiu evidenciar diferenças aromáticas entre os espumantes elaborados com leveduras Saccharomyces e não-Saccharomyces e novos estudos deverão avaliar outras características dos espumantes como estabilidade proteica e formação de espuma, com o intuito de melhorar o perfil dos espumantes nacionais.
Keywords: Vinhos espumantes - Serra, Região (RS); Leveduras; Fermentação; Bebidas fermentadas; Compostos aromáticos; Sparkling wines - Serra, Região (RS) (Brazil); Yeast; Fermentation; Brewing; Aromatic compounds